KEUNGGULAN KOMPETITIF MELALUI CITA RASA, PRODUK DESAIN, DAN PENDISTRIBUSIAN (Studi kasus pada Pempek Palembang Gaby Bekasi) - Rahmi Rosita; Enny Diah Astuti; Retno Setya Budiasningrum (JURNAL LENTERA BISNIS, 2025)
This research aims to determine the variable influence of brand image, product design and distribution on Pempek gaaby products in Bekasi. The research uses a quantitative method, which is also known as a statistical approach with SPSS tools, using a multiple linear regression method by distributing closed questionnaires to 100 respondents who visited Pempek gaby. The SPSS output results show that taste, product design and distribution have a positive impact on competitive adventage.